Application of bedside real-time tracheal ultrasonography for confirmation of emergency endotracheal intubation in patients in the intensive care unit. Issue 4 (October 2020) - Chen, Weiting; Chen, Junbo; Wang, Hehao; Chen, Yingzi
Objective: Critically ill patients often require emergency endotracheal intubation and mechanical ventilation. When esophageal intubation is not confirmed early, treatment may be delayed, even for life-threatening conditions. We examined the accuracy of bedside real-time airway ultrasonography in confirming the endotracheal tube (ETT) position during emergency endotracheal intubation in patients in the intensive care unit (ICU). Methods: This single-center prospective observational study included 118 patients who underwent urgent endotracheal intubation in the ICU of Taizhou Hospital of Integrated Traditional Chinese and Western Medicine. Tracheal ultrasonography was used to confirm the ETT position during endotracheal intubation, after which fiberoptic bronchoscopy was performed. The accuracy of bedside real-time tracheal ultrasonography in determining the ETT position was examined. Results: Twelve (10.2%) patients underwent endotracheal intubation. The kappa value was 0.844, indicating perfect consistency between tracheal ultrasonography and fiberoptic bronchoscopy in identifying esophageal intubation. The sensitivity, specificity, and positive and negative predictive values of tracheal ultrasonography in determining the ETT position were 75.0%, 100%, 100%, and 97.2%, respectively. Conclusions: Bedside real-time tracheal ultrasonography accurately assesses the ETT position in the ICU and can identify the ETT position during intubation. These findings have important clinical applications and are of great significance for treatment of ICU patients.